Live imaging of ERK signalling dynamics in differentiating mouse embryonic stem cells - Deathridge, Julia (Development, 2019)
Stimulation of the ERK/MAPK pathway is required for the exit from pluripotency and onset of differentiation in mouse embryonic stem cells (ESCs). The dynamic behaviour of ERK activity in individual cells during this transition is unclear. Using a FRET-based biosensor, we monitored ERK signalling dynamics of single mouse ESCs during differentiation. ERK activity was highly heterogeneous, with considerable variability in ERK signalling between single cells within ESC colonies. Different triggers of differentiation induced distinct ERK activity profiles. Surprisingly, the dynamic features of ERK signalling were not strongly coupled to loss of pluripotency marker expression, regardless of the differentiation stimulus, suggesting the normal dynamic range of ERK signalling is not rate-limiting in single cells during differentiation. ERK signalling dynamics were sensitive to the degree of cell crowding and were similar in neighbouring cells. Sister cells from a mitotic division also showed more similar ERK activity, an effect that was apparent whether cells remained adjacent or moved apart after division. These data suggest a combination of cell lineage and niche contributes to the absolute level of ERK signalling in mouse ESCs.